2020
DOI: 10.1103/physrevapplied.13.034001
|View full text |Cite
|
Sign up to set email alerts
|

Electron Acceleration in Direct Laser-Solid Interactions Far Beyond the Ponderomotive Limit

Abstract: In laser-solid interactions, electrons may be generated and subsequently accelerated to energies of the order-of-magnitude of the ponderomotive limit, with the underlying process dominated by direct laser acceleration. Breaking this limit, realized here by a radially-polarized laser pulse incident upon a wire target, can be associated with several novel effects. Three-dimensional Particle-In-Cell simulations show a relativistic intense laser pulse can extract electrons from the wire and inject them into the ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…We also note here that within or beyond the ponderomotive limit, energy gain of GeV magnitude can also be realized in other various regimes, see Refs. [35,44,45]. Note that, in contrast to full-pulse interactions, in half-pulse interactions the initial phase of electrons, i.e., position, is of importance for the energy gain, as shown in Figs.…”
Section: B Optimizing the Waist Of Gaussian Pulsesmentioning
confidence: 97%
“…We also note here that within or beyond the ponderomotive limit, energy gain of GeV magnitude can also be realized in other various regimes, see Refs. [35,44,45]. Note that, in contrast to full-pulse interactions, in half-pulse interactions the initial phase of electrons, i.e., position, is of importance for the energy gain, as shown in Figs.…”
Section: B Optimizing the Waist Of Gaussian Pulsesmentioning
confidence: 97%
“…In this bubble regime DLA and LWFA are affected mainly by overlapping of laser field with electrons and enough transverse momentum of injected electrons. It has been shown that these conditions are maintained by using a circularly polarized laser pulse instead of linearly polarized one [43]. The laser plasma interaction will efficiently accelerate electrons by applying an external magnetic field [44].…”
Section: Pulse Width Variation and The Excited Wake Field Profilesmentioning
confidence: 99%
“…Practically, it is fulfilled when τ 0 ≲ 1.3λ/c, see the results for τ 0 = 3 fs. In the same manner, single electron attobunch can be generated employing different configurations of the laser pulse interaction with the overdense target [40,41]. • In the case of longer pulses, another option is controlling the laser intensity.…”
Section: Spectra Of Respective Attosecond Bunches and Generation Of A Single Bunchmentioning
confidence: 99%